2013
DOI: 10.1016/j.neuron.2013.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Induced Convergence of APP and BACE-1 in Acidic Microdomains via an Endocytosis-Dependent Pathway

Abstract: The convergence of APP (substrate) and BACE-1 (enzyme) is a rate-limiting, obligatory event triggering the amyloidogenic pathway – a key step in Alzheimer’s disease (AD) pathology. However, as both APP/BACE-1 are highly expressed in brain, mechanisms precluding their unabated convergence are unclear. Exploring dynamic localization of APP/BACE-1 in cultured hippocampal neurons, we found that after synthesis via the secretory-pathway, dendritic APP/BACE-1-containing vesicles are largely segregated in physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
222
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(249 citation statements)
references
References 42 publications
26
222
1
Order By: Relevance
“…SORL1 acts as a retention factor for APP in the TGN and thus regulates APP trafficking (5). Some reports have implicated the endosomes in this process, but endosomal function could be affected by altered Golgi-mediated trafficking under disease conditions (6,7). Furthermore, several recent reports have suggested that the amyloidogenic processing of APP, which produces Aβ, may occur in the Golgi and the late secretory pathway (2,4).…”
mentioning
confidence: 99%
“…SORL1 acts as a retention factor for APP in the TGN and thus regulates APP trafficking (5). Some reports have implicated the endosomes in this process, but endosomal function could be affected by altered Golgi-mediated trafficking under disease conditions (6,7). Furthermore, several recent reports have suggested that the amyloidogenic processing of APP, which produces Aβ, may occur in the Golgi and the late secretory pathway (2,4).…”
mentioning
confidence: 99%
“…We hypothesized that the decrease in BACE1 protein levels was a result of increased trafficking of BACE1 to the lysosomes and reduction of BACE1 in recycling endosomes, the intracellular site where BACE1 meets and processes APP (55)(56)(57). We found that USP8 depletion increased BACE1 localization in the early endosomes and the lysosomes, while decreasing BACE1 contained in the recycling endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry staining also showed Aβ42 were existed in AEL (autophagy-endosomal-lysosomal) vesicles in Drosophila neurons [62]. Another study applied on neuron showed that although APP and its processing enzyme BACE1 should be separated into distinct vesicles under normal condition, they showed strong co-localization and co-trafficking into autophagy-lssosome pathways under glycine/ NMDA-receptor agonist /K+ or GABA A antagonist Picrotoxin (PTX) stimulations [63]. This result indicated under some certain pathological conditions, the convergence of APP and BACE1 in autophagosomes may perform as novel place for Aβ generation.…”
Section: Autophagy Dysfunction and Ad-related Pathologymentioning
confidence: 98%